일부 유아교육기관 교사의 구강보건지식 및 실천정도 분석 - 김수화; Soo Hwa Kim; 임미희; Mi Hee Lim; 정재연; Jae Yeon Jung; 황윤숙; Yoon Sook Hwang; 이선미; Sun Mi Lee (Chiwisaeng gwahakoeji, 2010)
The purpose of this study was to examine the oral health knowledge and oral health practice of teachers in early childhood education institutions. The subjects in this study were 169 teachers who worked in early childhood education institutions. After a survey was conducted, the collected data were analyzed with a SPSSWIN 14.0 program. The findings of the study were as follows: 1. Concerning oral health knowledge, they got a mean of 7.97(9), 2.66(3), 2.86(5), 2.42(5) and 1.04(2) respectively in knowledge on dental caries, toothbrushing, periodontitis, fluoride and diet. Overall, they got a mean of 16.98 in 24 items, and the score corresponded to approximately 70 out of 100 points. 2. As for oral health practice, tongue cleaning(4.22) was what they did the most to take care of their oral health, and they just got 2.60 in regular dental checkup. Overall, they got about 3.11 in oral health practice. 3. Regarding relationship between general characteristics and oral health knowledge, the teachers who were in their 30s got 17.47 in overall oral health knowledge, and those with a career of five to less than 10 years got 17.50. The teachers who received college or higher education got 17.27, and the principals got 18.26. Those who had ever received education on oral health got 17.01. But the gaps between them and the others were not statistically significant. 4. As to connections between general characteristics including age and oral health practice, restricted sugar intake, regular dental checkup, the use of oral hygiene supplies, tongue cleaning and overall oral health practice were more prevailing among the older teachers, and the gaps between them and the younger teachers were statistically significant. 5. In terms of relationship between oral health knowledge and oral health practice, there was no statistically significant relationship between the two on the whole, but better oral health knowledge led to better oral health practice in each part. This study shows that various oral health education programs for the kindergarten teachers should be developed and continuous education through the programs is important to improve the knowledge of oral health and to change oral health behavior. 본 연구는 유아교육기관 교사의 구강건강지식 및 구강건강실천정도를 파악하고자 유아교육기관에서 근무하고 있는 교사 169명을 대상으로 설문조사 하였으며, SPSSWIN 14.0을 이용하여 분석한 결과 다음과 같은 결론을 얻었다. 1. 구강건강지식정도에 있어서 치아우식증 관련지식 평균 7.97(9), 잇솔질 2.66(3), 치주조직병 2.86(5), 불소 2.42(5), 식이 1.04(2)로 나타났으며, 전체 24문항을 기준으로 평균 16.98로 100점으로 환산시 70점 정도의 구강건강지식 수준을 보였다. 2. 구강건강실천정도는 혀닦기를 하는 경우가 4.22로 가장 높은 반면, 정기구강검진에 있어서는 2.60으로 낮게 나타났다. 전체 구강건강실천정도는 3.11정도의 수준을 보였다. 3. 일반적 특성에 따른 구강건강지식과의 차이는 전체적인 지식에 있어 30대 연령 17.47, 5년 이상-10년 미만의 교육경력 17.50, 대졸이상 17.27, 원장인 경우가 18.26, 교육경험이 있는 경우가 17.01로 높게 나타났으나 통계적으로 유의한 차이는 없었다. 4. 일반적 특성에 따른 구강건강실천정도와의 차이는 연령에 있어서 당분섭취제한, 정기구강검진, 구강위생보조용품사용, 혀닦기, 전체적인 구강건강실천정도에 있어 나이가 많을수록 실천정도가 높은 것으로 나타났고, 통계적으로도 유의한 차이를 보였다. 5. 구강보건지식정도와 구강건강실천정도와의 관계는 전체적으로 통계적으로 유의한 차이는 없었지만 각 영역별로 구강보건지식이 높을수록 실천정도가 높음을 확인할 수 있었다. 이상의 결과로 교사들을 대상으로 한 다양한 구강보건교육 프로그램이 개발되어 지속적인 구강보건교육을 통한 지식의 향상은 물론 구강보건실천 향상도 매우 중요하다고 사료된다.